2012
DOI: 10.1371/journal.pone.0033236
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of Patients with Preventable Adverse Drug Reactions and Preventability of Adverse Drug Reactions – A Meta-Analysis

Abstract: Background Numerous observational studies suggest that preventable adverse drug reactions are a significant burden in healthcare, but no meta-analysis using a standardised definition for adverse drug reactions exists. The aim of the study was to estimate the percentage of patients with preventable adverse drug reactions and the preventability of adverse drug reactions in adult outpatients and inpatients. Methods Studies were identified through searching Cochrane, CINAHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
181
2
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(208 citation statements)
references
References 49 publications
15
181
2
10
Order By: Relevance
“…208 The WHO has identified some key areas including measuring harm, understanding causes, identifying solutions, evaluating impact and translating evidence into safer care. Hakkarainen et al 211 conducted a meta-analysis of preventable ADR studies and they concluded that preventable ADRs are a significant burden to the health-care system and a cause of morbidity among outpatients, and that roughly half of all ADRs in adults both inpatients (45%) and outpatients (52%) may be preventable.…”
Section: Introductionmentioning
confidence: 99%
“…208 The WHO has identified some key areas including measuring harm, understanding causes, identifying solutions, evaluating impact and translating evidence into safer care. Hakkarainen et al 211 conducted a meta-analysis of preventable ADR studies and they concluded that preventable ADRs are a significant burden to the health-care system and a cause of morbidity among outpatients, and that roughly half of all ADRs in adults both inpatients (45%) and outpatients (52%) may be preventable.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that majority of ADRs are preventable. 2 The incidence and severity of ADRs can be influenced by age, gender, concurrent renal , hepatic disease, genetic factors, type of drug, route of administration, duration of therapy, and dosage. 3,4 Paediatric patients constitute a vulnerable group with regard to rational drug prescribing.…”
mentioning
confidence: 99%
“…Estes eventos nocivos são denominados Reações Adversas a Medicamentos (RAM) e sua elevada incidência representa um grande impacto nos sistemas de saúde. Estudos mostram que 2% a 30% das admissões em serviços de emergência estão relacionadas à ocorrência de RAM (2,3). Além disso, estes eventos também são responsáveis por uma parcela significativa dos custos durante a hospitalização e podem aumentar o tempo de internação e a mortalidade (3).…”
Section: Introductionunclassified